Effective Mechanical Properties of Additive Manufactured Strut‐Lattice Structures: Experimental and Finite Element Study. Issue 3 (28th October 2021) - Kladovasilakis, Nikolaos; Tsongas, Konstantinos; Kostavelis, Ioannis; Tzovaras, Dimitrios; Tzetzis, Dimitrios
Abstract : Current developments in additive manufacturing (AM) technologies enable the fabrication of complex geometries with a variety of materials. Utilizing AM techniques, lattice structures are usually employed for the topology optimization (TO) process in various industries. Therefore, it is essential to identify the effective mechanical behavior of the lattices and establish finite element (FE) models capable to evaluate their performance. This research focuses on four lattice structures consisted of struts, two structures for foam‐like applications, namely, Kelvin and Weaire–Phelan structures, and two geometries for structural applications, that is, octet and rhombic dodecahedron structures. Herein, a theoretical approach is employed for each structure to present the basic structural properties and connect their design‐related parameters, such as unit cell's length and strut thickness, with the relative density of each geometry. In addition, unit cells of each structure are manufactured utilizing selective laser sintering AM technique with Polyamide 12 as construction material. Compression tests are performed to identify the mechanical behavior of each geometry through representative volume elements and FE hyper‐elastic material models are developed accordingly to the experimental data. Finally, more complex specimens of each geometry are fabricated and tested to verify the accuracy and the reliability of the FE models. Abstract : Four different strut‐lattice structures (Kelvin, Rhombic dodecahedron, Weaire‐Phelan and Octet) were SLS 3D printed and tested under uniaxial compression. Also, theoretical analyses were performed for the lattices and approximation equations were proposed connecting design‐related parameters with relative density. Overall, the mechanical behavior of lattice RVEs can be extracted by FE models that assess the mechanical response of more complex structures.